In Vitro Analysis of SARS-CoV-2 Variants that Caused Severe COVID-19 in the Elderly - Sutandhio, Silvia; Wihanto, Laura; Tedyanto, Cecilia Putri; Santoso, Sentot (Indonesian Journal of Tropical and Infectious Disease, 2025)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) caused the global problem of respiratory disease from 2019 to 2024. One of the earliest variations in the SARS-CoV-2 S protein was the S D614G mutation. SARS-CoV-2 has several important variants, namely, Alpha, Beta, Gamma, Delta, and Omicron. Omicron is the variant that has caused severe health problems, someresulting in death, in the elderly. Omicron has further differentiated to some wellknown variants, such as, BA.1, BA.2, BA.2.75, BA.5, BQ.1.1, and XBB.1. According to Japanese Government data, the number of citizens aged 65 years old and above reached 28.9% in 2021. From our previous experiment, antibodies of the elderly that have received four doses of mRNA vaccine still could not optimally neutralize Omicron BQ.1.1 and XBB.1. We aimed to analyze the plaque size of SARS-CoV-2 variants that caused severe COVID-19 in the elderly. SARS-CoV-2 variants were seeded in Vero E6-TMPRSS2 cell culture to create plaques. The resulting plaques were analyzed with ImageJ application to select solitary plaques and to determine plaque sizes. The size of BA.1 plaque was indifferent to BA.2 plaque. The plaque area comparison result was as follows, BA.1/BA.2<BA.5<BA.2.75<BQ.1.1<XBB.1. The plaque sizes of Omicron BQ.1.1 and XBB.1 were bigger that those of Omicron BA.1 and BA.2. The plaque sizes of all Omicron variants were smaller than those of the previousvariants, S D614G and Delta. The result of this in vitro experiment inferred that there is increase in fusogenicity of BQ.1.1 and XBB.1, when compared with BA.1 and BA.2.